Contamination of Escherichia coli, Salmonella sp. and Vibrio sp. on ice cubes at food stalls in Karangasem Regency, Bali Province in 2021 - I Gede Wikania Wira Wiguna; Agus Eka Darwinata; Komang Januartha Putra Pinatih; Ni Nengah Dwi Fatmawati (DiscoverSys Inc., 2022)
Background: Waterborne diseases spread through drinking water and food products made from drinking water, including cooking utensils that are washed using contaminated water. Ice cube is widely used by the people in Indonesia. There was no study regarding bacteria contamination on an ice cube in Karangasem Regency. This study aimed to determine the contamination of Escherichia coli, Salmonella sp., and Vibrio sp. on ice cubes at food stalls in Karangasem Regency in 2021. Methods: This study used a cross-sectional research design and simple purposive sampling as the sampling technique. Ice cubes were taken from 42 food stalls from eight sub-districts. Samples were cultured on Lactose Broth (LB) media for the Most Probable Number (MPN) test procedures and Eosin Methylene Blue Agar (EMBA) to identify the presence of E. coli, Salmonella Shigella Agar (SSA) for Salmonella sp., and Thiosulfate Citrate Bile Sucrose (TCBS) for Vibrio sp. and followed by gram staining. Data processing was carried out descriptively to determine the percentage of samples with positive contamination. Data were analyzed using Microsoft Excel version 2010 for Windows. Results: Based on the study results, it was found that all samples contained coliform bacteria through the MPN test (100.0%). In addition, 5 samples (11.9%) were found positive for E. coli. While the identification of Salmonella sp. and Vibrio sp was found no positive results. Conclusions: There was coliform bacteria contamination in the tested ice cube samples. In addition, E. coli was found in the sample; however, there were no Salmonella sp. and Vibrio sp. on ice cube samples.